The Sister Arts: Ekphrasis and Enargeia as Metaphorical Processes of an Unfinished Art-Historical Discourse - Di Paola, Modesta (Escritura e Imagen, 2025)
This paper examines how, throughout art history, images and language have maintained constant relationships with each other, from Antiquity to the interartistic phenomena that characterise much of contemporary artistic production. This relationship between image and language can be understood through the concept of metaphoricity: the ability of images to operate metaphorically within verbal discourse. From this perspective, we will study ekphrasis and enargeia, resources that demonstrate how different arts influence each other, in line with the ancient notion of the “sister arts”. Likewise, this study revisits Lessing’s famous distinction between the spatial arts and the temporal arts, a classification that was challenged by numerous artists and poets who transgressed these boundaries. Finally, we highlight how contemporary visual studies and visual rhetoric have promoted a comparative approach that identifies common rhetorical figures between verbal language and image.